The Socio-Economic Life of Coastal Fishing Communities in Kalar-Kalar Village, South Aru Subdistrict, Aru Islands Regency - Benamen, Yunita Yulia; Dokolamo, Hamid (Universitas Pattimura, 2024)
Indonesia, as the largest archipelagic country in the world, boasts extraordinary marine resources, including over 8,500 fish species. Coastal fishing communities play a crucial role in the economy and the sustainability of marine ecology. This study focuses on the fishing community in Kalar-Kalar Village, Aru Islands Regency, where the majority of the population works as fishermen with limited education and dependence on traditional fishing gear. The aim of this study is to analyze the socio-economic conditions of coastal fishing communities using a comprehensive approach, including factors affecting the fishermen's welfare and adaptation strategies used to overcome economic and environmental challenges. The research method employed is qualitative with a descriptive approach. Primary data were obtained through observations and in-depth interviews with various informants, while secondary data were collected from relevant documents, reports, and statistics. The results indicate that limited access to modern technology, education, and healthcare hinders the productivity and welfare of the fishing community. Conflicts between large and small fishermen over the dominance of fishing areas were also identified as a major issue. This study concludes that more effective government intervention, including assistance programs, guidance, and capacity building for fishermen, is necessary to improve their welfare